Pulmonary Artery Aneurysm Dilemma in Pregnancy: A Case Report - Shadi Zamansaraei; Milad Nazari Sabet; Parvin Bahrami (Case Reports in Clinical Practice, 2023)
Pulmonary Artery Aneurysm (PAA), defined as greater than 40 mm dilation of the main pulmonary artery wall, in female and above 43 mm in males is a rare and fatal defect. Since there is a high risk for rupture, especially in cases of symptomatic or severe dilatation, surgical intervention is suggested. There is no recommendation about therapeutic methods based on the diameter of the pulmonary aneurysm in pregnancy in the guidelines. In this rare and unique report, we described a 26-year-old pregnant woman with previous history of biologic pulmonary valve replacement referred to the joint clinic of heart disease and pregnancy at 15 weeks of pregnancy because transthoracic echocardiography showed an aneurysm of the main pulmonary artery (55mm). Due to pulmonary artery diameter and risk of dissection, we informed her about the risks and recommended therapeutic abortion, but she refused and, fortunately no complication occurred during close observation in pregnancy and few months later. There is no specific recommendation about therapeutic methods based on the diameter of the pulmonary aneurysm in pregnancy in the guidelines, but referring to the aortic aneurysm guidelines recommendation, pregnancy termination when PA diameter > 5.5 cm because of the higher risk of dissection. Other factors should be considered to determine the risk of dissection in pregnancy include; categorized PA aneurysms to high or low intravascular PA pressure, PA diameter growth rate, and causative mechanisms. Thus, if pregnancy occurs, decisions about each patient will vary depending on risk factors